Gelatinous Marrow Transformation in Chronic Myeloid Leukemia Post-Dasatinib Treatment: A Case Report with Review of Literature - Kini, Gayathri; Bhandary, Chandni; Vivekananda, Poornachandra; Jayaprakash, Chandrashekhar S. (Indian Journal of Medical and Paediatric Oncology, 2025)
Gelatinous marrow transformation (GMT) is characterized by accumulation of extracellular gelatinous substances such as mucopolysaccharides, fat cell atrophy, and focal loss of hematopoietic cells. It is a rare disorder of unknown pathogenesis. Anorexia nervosa, acute febrile state, acquired immunodeficiency syndrome, heart failure, lymphomas, and carcinomas are some of the entities associated with GMT. A 57-year-old male patient presented with abdominal distension of 1-month duration. He was diagnosed as chronic myeloid leukemia (CML) and treated with imatinib. Repeat testing 2 years later revealed a normal hemogram. However, in view of his BCR::ABL1 levels of 17%, he was switched to dasatinib. Patient presented with fever, fatigue, and reduced appetite 4 months later. Hemogram revealed pancytopenia. Bone marrow examination showed a hypocellular marrow with trilineage suppression and gelatinous transformation. GMT in CML patients' posttherapy is a rare encounter. It is essential to identify this clinical scenario for optimal patient management and monitoring progression of disease.
Keywords: dasatinib; gelatinous marrow transformation; chronic myeloid leukemia; case report